International cost-effectiveness analysis in osimertinib after chemoradiotherapy in stage III EGFR-mutated non-small cell lung cancer - Tang, Diya; Zou, Xi; Wei, Chaochao; Zhang, Xiaoyu (Frontiers in Public Health, 2025)
BackgroundThe international Phase 3 LAURA trial (NCT03521154) demonstrated that the use of osimertinib following chemoradiotherapy markedly improved survival outcomes in unresectable stage III NSCLC with epidermal growth factor receptor (EGFR) mutations. Considering the high cost of targeted therapy, the popularization of osimertinib in clinical practice should be considered comprehensively in terms of cost and efficacy. This study was to investigate the cost-effectiveness of osimertinib for unresectable stage III EGFR-mutated NSCLC without disease progression after chemoradiotherapy from the perspective of payers in the USA and China.MethodsThe main health outcomes were evaluated by measuring life-years (LYs), quality-adjusted life-years (QALYs), incremental cost-effectiveness ratio (ICER), and incremental net health benefit (INHB). An integrated Markov model with three separate health states over a 15-year horizon was established. The sensitivity of the model was assessed, and subgroup analyses were conducted.ResultsCompared with placebo in stage III EGFR-mutated NSCLC after chemoradiation, osimertinib [$898,107 (3.70 QALYs) and $49,565 (3.49 QALYs)] increased costs (efficacy) by $178,953 (0.56 QALYs) in the USA and $17,872 (0.51 QALYs) in China. The corresponding ICERs were $322,308/QALY and $35,186/QALY, respectively, with an INHB of −0.63 and 0.06 QALYs. The sensitivity analysis showed that the results were influenced significantly by progression-free survival.ConclusionsIn China, treatment with osimertinib rather than placebo appears to be an effective and economically accessible option for patients with stage III EGFR-mutated NSCLC with no disease progression after chemoradiotherapy. This applied especially to the eastern and central economic regions of China but not the USA currently.